PRAGMATIC DEFICITS OF ASPERGER SYNDROME - Humaira’, Silmy Arizatul (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2015)
Human being is social creature who needs other people to interact with. One of the ways to interact with others is communication with language. However, communication could be a complicated problem for those who were born with developmental disorder called Asperger Syndrome (AS). The communication challenge of Asperger’s is the difficulty using language appropriately for social purposes or known as pragmatic deficits. Many excellent books about autism are published whereas knowledge on pragmatic deficits are still very limited. Thus, it is expected to be a beneficial reference to understand the pragmatic deficits and to create strategies for them to communicate effectively. Therefore, this study aimed at exploring the kinds of pragmatic deficits of an individual with AS. The verbal language profiles of autism purposed by MacDonald (2004) is used to analyzed the data in depth. The descriptive qualitative method is applied to develop a comprehensive understanding about the AS case in Temple Grandin movie.The finding shows that all of the five types of communication deficits are appearing and the dominant of which is unresponsive.